2013
DOI: 10.5021/ad.2013.25.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Extramammary Paget's Disease of External Genitalia with Bowenoid Features

Abstract: Extramammary Paget's disease (EMPD) is an uncommon intraepithelial adenocarcinoma, primarily affecting the apocrine-bearing skin. Bowen disease is an intraepithelial squamous cell carcinoma having the potential to become invasive carcinoma. The histopathological concomitant features between EMPD and Bowen disease have been described. One theory is that primary EMPD arises multicentrically, within the epidermis from the pluripotent stem cells. Herein, we describe a case of EMPD that had bowenoid features, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Squamous cell carcinoma or BCC coexistent with EMPD is very rare; our research identified 13 reported cases so far . Three main hypotheses have been proposed for their coexistence among the authors, as follows: (i) EMPD has the potential for metaplastic change into CSCC/Bowen's disease (BD); (ii) the tumors were derived from a common progenitor cell; (iii) the tumors occurred independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Squamous cell carcinoma or BCC coexistent with EMPD is very rare; our research identified 13 reported cases so far . Three main hypotheses have been proposed for their coexistence among the authors, as follows: (i) EMPD has the potential for metaplastic change into CSCC/Bowen's disease (BD); (ii) the tumors were derived from a common progenitor cell; (iii) the tumors occurred independently.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma or BCC coexistent with EMPD is very rare; our research identified 13 reported cases so far. [1][2][3][4][5][6][7][8][9][10][11][12][13] Three main hypotheses have been proposed for their coexistence among the authors, as follows: (i) EMPD has the potential for metaplastic change into CSCC/Bowen's disease (BD); (ii) the tumors were derived from a common progenitor cell; (iii) the tumors occurred independently. The authors who suggested hypotheses (i) or (ii) base their case on the fact that there were tumor cells showing both cell type characteristics morphologically and immunohistochemically.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions produced by PPD are similar in appearance to a number of other skin lesions including dermatitis, lichen simplex, psoriasis, eczema, leukoplakia, Bowen’s disease, pagetoid melanoma, basal and squamous cell carcinoma, condylomata acuminata, mycosis fungiodes and the epidermal phase of neuroendocrine carcinoma 3 5 6…”
Section: Differential Diagnosismentioning
confidence: 91%
“…Esta distinció n es aú n má s difícil cuando solo pequeñ as biopsias superficiales está n disponibles para su interpretació n, ya que en la actualidad se tiende a dar mayor é nfasis a los resultados cosmé ticos con varias té cnicas «má s rá pidas y menos traumá ticas» que al diagnó stico preciso [6][7][8][9] . Esta distinció n es aú n má s difícil cuando solo pequeñ as biopsias superficiales está n disponibles para su interpretació n, ya que en la actualidad se tiende a dar mayor é nfasis a los resultados cosmé ticos con varias té cnicas «má s rá pidas y menos traumá ticas» que al diagnó stico preciso [6][7][8][9] .…”
unclassified
“…En algunos casos es imposible la diferenciació n histopatoló gica de ambos procesos y los estudios de IHQ facilitan la diferenciació n. Las cé lulas en PSCCIS son negativas para citoqueratina 7 y CEA, y las cé lulas en el EPEM son positivas para estos inmunomarcadores [6][7][8][9] . En ambos casos se observan abundantes cé lulas pá lidas en toda la epidermis.…”
unclassified